SURGICAL MANAGEMENT OF AURAL HEMATOMA IN A GERIATRIC CAT: A CASE REPORT - Muhammad Farid Rizal; Hilma Luthfia Sudarsyah; Hadrianus Lau; Retina Yunani; Reinier Melvern; Garini Maura Maharani Sunartoputri; Felicia Maharani; Itfa Alya (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Aural hematoma is a common auricular condition in small animals, particularly cats and dogs, often associated with trauma or otitis externa. Geriatric cases present added clinical complexity challenges due to concurrent systemic conditions and anesthetic risks. A 13-year-old sterilized male domestic cat with gray hair color, named Ali, was brought by its owner to the veterinary clinic (Urban Animal Pet Care Clinic, Bandung, Indonesia) with right auricular swelling and erythema and left auricular abscess rupture. Clinical evaluation revealed an aural hematoma of the right pinna and a ruptured abscess on the left. Hematological and biochemical analysis indicated leukocytosis, elevated BUN and creatinine, and hyperglobulinemia, suggesting chronic inflammation and mild renal impairment. Management included surgical correction of the aural hematoma using the button suture technique and debridement with drainage of the contralateral auricular abscess. Anesthetic dosing was adjusted considering the patient’s geriatric status; the standard Zoletil dose of 0.1 mg/kg BW IM was reduced to 0.05 mg/kg BW IM to minimize cardiovascular depression and other potential anesthetic complications. Perioperative fluid therapy was also carefully tailored to the patient’s systemic condition. Sutures and bandaging were removed on postoperative day 10 with satisfactory healing and no recurrence. Postoperative management carried out with ciprofloxacin as antimicrobial agent, dipyrone as analgesic and anti-inflammatory, and Channa striata extract aided recovery. The button suture technique represents an effective and minimally deforming surgical approach for aural hematoma in geriatric cats, especially when combined with tailored anesthetic management and postoperative management. This case emphasizes the importance of individualized treatment strategies in elderly feline patients with concurrent systemic conditions. It is important to install a collar from the beginning of the therapy process for the patient. This aims to help accelerate the healing process.